PENGABDIAN MASYARAKAT PENERAPAN SARINGAN AIR BAGI MASYARAKAT DI DESA BOJONGMALAKA KECAMATAN BALEENDAH KABUPATEN BANDUNG - Martoni; Dani Hamdani; Sri Lestari (Jurnal Ilmiah Teknologi Infomasi Terapan, 2022)
In the Bojongmalaka area, the people have difficulty with clean water. The water condition there is murky and yellow so it is not suitable for use. On the basis of that problem, the executor of community service grant from Widyatama University collaborated between Mechanical Engineering study program and Information Systems Study program to try to serve the community to solve this clean water problem and the result is a water filter applied to Bojongmalaka village community with the hope of helping solve the problem of clean water in the village of Bojongmalaka. This activity involves lecturers and students at Widyatama University. Stages of Implementation of Devotion is done with Problem Identification, Tool Making, Socialization, Implementation, Assistance and Evaluation, Evaluation of program implementation, Program Sustainability. Based on the questionnaire distributed to the community, 51 % of the community used digging wells, 63 % treated the water so that it was safe to drink, and 88.9 % of the water was clear, odorless. Bojongmalaka village head Dedi Dermawan and residents are very enthusiastic about this activity can help the problems faced by residents. The head of Bojongmalaka village thanked Widyatama University and the Director-General of Dikti Ristek for their funding in 2021. Dedi hoped that similar activities could be continued for other problems in Bojongmalaka village..